2019
DOI: 10.1088/2043-6254/ab1cb3
|View full text |Cite
|
Sign up to set email alerts
|

Formation of silver nanoparticles and their application for suppressing surface reflection ofn-type silicon

Abstract: In this paper silver-assisted chemical etching (SACE) was studied to increase roughness and reduce light reflection from the surface of n-type (100) mono-crystalline silicon. SACE process includes two basic steps which are silver deposition and chemical etching step. Simple electroless silver deposition step using mixture of AgNO 3 and HF was utilized to form silver nanoparticles onto n-type silicon surface. Following chemical etching step was carried out by immersing samples in mixture of HF and H 2 O 2 . Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Silicon nanowires (Si NWs ) have gained interest in the last few years due to their versatility and properties like absorption, light emission, catalytic activity, and a wide range of applications. Among all its applications, they can be exploited for photocatalysis, [7][8][9][10] solar water splitting, 11,12 detection of molecules, [13][14][15] light trapping, 16,17 reduction of metals, 18 storage and energy conversion, 19 CO 2 reduction, 20,21 hydrogen generation, 22 and many other applications. Moreover, it has been reported that the decoration of silicon nanowires with metallic nanoparticles can enhance their catalytic properties, especially for electron discharging.…”
Section: Introductionmentioning
confidence: 99%
“…Silicon nanowires (Si NWs ) have gained interest in the last few years due to their versatility and properties like absorption, light emission, catalytic activity, and a wide range of applications. Among all its applications, they can be exploited for photocatalysis, [7][8][9][10] solar water splitting, 11,12 detection of molecules, [13][14][15] light trapping, 16,17 reduction of metals, 18 storage and energy conversion, 19 CO 2 reduction, 20,21 hydrogen generation, 22 and many other applications. Moreover, it has been reported that the decoration of silicon nanowires with metallic nanoparticles can enhance their catalytic properties, especially for electron discharging.…”
Section: Introductionmentioning
confidence: 99%
“…Some etching mechanisms have been proposed to explain the MACE process. A reduction reaction for the cathodic process implies the decomposition of H 2 O 2 at the metallic surface in acidic conditions [46][47][48][49][50].…”
Section: Reactions Of the Mace Anisotropic Wet Etching Process For Si...mentioning
confidence: 99%